Development and calibration of a new mathematical model for the description of an ion-exchange process for ammonia removal in the presence of competing ions. (1st November 2021) - Lizarralde, I.; Guida, S.; Canellas, J.; Jefferson, B.; Grau, P.; Soares, A.
Highlights: Calibration of a mathematical model for the description of ion-exchange process. Nitrogen removal with ion-exchange process under competing ions. Exploration of ion-exchange process under different operating conditions. Abstract: Ammonia ion removal and recovery via an ion-exchange process using zeolites is a promising alternative to traditional biological treatments. The analysis of its efficiency is not straightforward as it depends on various factors, such as the cation exchange capacity of the zeolite, amount of zeolite available, initial ammonia concentration, contact time, ammonia speciation depending on pH or the presence of competing ions. Mathematical modelling and simulation tools are very useful to analyse the effect of different operational conditions on the efficiency and optimal operation of the process. This paper experimentally analyses the effect that the presence of competing ions has on the efficiency of ammonia removal. This experimental work has shown a reduction of around 21% of ammonia removal efficiency in the presence of competing ions. The main contribution of this paper is the development new mathematical model able to describe the ion-exchange process in the presence of competing ions. The mathematical model developed is able to analyse the performance of the IEX process under different empty bed contact times, influent loads, pH and concentrations of competing ions. The capability of the model to reproduce real data has been proven comparing the experimental and simulation results. Finally, an exploration by simulation has been undertaken to show the potential of the mathematical model developed. Graphical abstract: Image, graphical abstract